MALIGNANT ARTERIAL HYPERTENSION IN A CHILD WITH ATYPICAL HEMOLYTIC-UREMIC SYNDROME - Зенченко, Олеся Алексеевна; Скударнов, Евгений Васильевич; Выходцева, Галина Ивановна; Волкова, Юлия Васильевна; Новикова, Людмила Михайловна; Малюга, Ольга Михайловна (Mother and Baby in Kuzbass, 2022)
Atypical hemolytic-uremic syndrome (aHUS) is a rare orphan disease. In the Altai Region, two cases of aHUS among children have been recorded. The disease is characterized by a severe course with high mortality, frequent development of complications and a possible outcome in the terminal stage of chronic renal failure. The severe course of aНUS may be aggravated by the development of extrarenal complications. In addition, patients with atypical hemolytic-uremic syndrome have a high risk of developing relapses of the disease - acute manifestations of aНUS. The presented clinical observation describes the unfavorable course of aHUS complicated by secondary malignant arterial hypertension.
Keywords: atypical hemolytic-uremic syndrome; acute renal injury; arterial hypertension; children